2011
DOI: 10.1007/s11739-011-0629-0
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate hospital admission: interaction between patient age and co-morbidity

Abstract: The aim of the study is to determine the prevalence of inappropriate admission, and to identify the factors that influence appropriateness of hospital admission. Data were prospectively collected from all 345 consecutive patients admitted during the period of 1 month for acute hospital care at a 110-bed division of internal medicine using socio-demographic and medical information. Statistical analyses included χ2 tests, t tests, and logistic regression analyses. According to the European version of the Appropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 22 publications
3
18
1
Order By: Relevance
“…This possibly refl ects not only the complex health and community needs of older people, but also their increased vulnerability to hospital admission due to comorbidities. A study in Italy 17 showed that while comorbidity increased the likelihood of an appropriate admission in young patients, the converse was true for older people.…”
Section: Resultsmentioning
confidence: 99%
“…This possibly refl ects not only the complex health and community needs of older people, but also their increased vulnerability to hospital admission due to comorbidities. A study in Italy 17 showed that while comorbidity increased the likelihood of an appropriate admission in young patients, the converse was true for older people.…”
Section: Resultsmentioning
confidence: 99%
“…Age and chronic illness may be specifically associated with appropriateness of hospitalization. In a recent study on appropriateness of hospital admission, age and co‐morbidity were not independently related to inappropriateness; however, when tested for interaction, inappropriateness was significantly more frequent at a young age in the absence of co‐morbidities and, numerically most relevant, in elderly patients when presenting with co‐morbidities [16]. In that single centre evaluation, co‐morbidity turned out to be an important determinant of age‐dependent appropriateness of hospital admission.…”
Section: Introductionmentioning
confidence: 86%
“…Whereas quite a few studies have found that a previous hospital admission were associated with a higher risk to be re-hospitalized [12, 14, 15], Roland and colleagues [16] found that having two or more admissions one year, proved to have a low sensitivity in detecting older patients who will have high admissions in the following year. Several studies underline that the severity of disease and the burden of comorbidity are strong predictors of hospitalizations [11, 12, 15, 17], and also that functional disability, cognitive impairment, as well as factors related to living conditions (i.e., low socio-economic level and social deprivation) also seem to play a part in frequency of hospitalizations for older persons [15, 18, 19]. …”
Section: Introductionmentioning
confidence: 99%
“…Other studies have identified that emergency hospital admissions often occurs when an older person has reached a point of crisis, due to a combination of circumstances; such as an exacerbation of a chronic condition, change in social setting, or a cascade of symptoms due to multi-morbidity and frailty [12, 17, 25, 26]. …”
Section: Introductionmentioning
confidence: 99%